2021
DOI: 10.1002/batt.202100018
|View full text |Cite
|
Sign up to set email alerts
|

Host‐Guest Interactions Enhance the Performance of Viologen Electrolytes for Aqueous Organic Redox Flow Batteries

Abstract: Host‐guest interactions are an attractive approach to design redox electrolytes, enabling to precisely tune the key properties for redox flow batteries such as half‐cell redox potential, solubility, and stability. Herein we report a host‐guest complex of highly water soluble (2‐hydroxypropyl)‐β‐cyclodextrin with 1‐decyl‐1′‐ethyl‐4,4′‐bipyridinium dibromide as anolyte in a new aqueous organic redox flow battery (AORFB). The supramolecular anolyte ensured the total RFB voltage increase of ≈9 % up to 0.97 V and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Aleksandr et al reported the host-guest interaction of viologen with (2hydroxypropyl)-b-cyclodextrin (HBCD) and use of this system yielded increased power density and battery life. 24 Lei et al reported the use of a-cyclodextrin (a-CD) as a molecular spectator for ethyl viologen and showed that a-CD avoids the dimerization of ethyl viologen and enhances the radical stability to a good extent. 25 Yeting et al reported the formation of a 1 : 1 supramolecular binary complex between viologen and CB [7] wherein the complexation shifted the reduction potential to a less negative value-and, as a result, an increase in the total cell voltage was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Aleksandr et al reported the host-guest interaction of viologen with (2hydroxypropyl)-b-cyclodextrin (HBCD) and use of this system yielded increased power density and battery life. 24 Lei et al reported the use of a-cyclodextrin (a-CD) as a molecular spectator for ethyl viologen and showed that a-CD avoids the dimerization of ethyl viologen and enhances the radical stability to a good extent. 25 Yeting et al reported the formation of a 1 : 1 supramolecular binary complex between viologen and CB [7] wherein the complexation shifted the reduction potential to a less negative value-and, as a result, an increase in the total cell voltage was observed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, EDV was used as a reference viologen compound since an impact of host−guest interactions on RFB properties for a modified anolyte containing EDV was previously described by us. 63 The solubilities (Figure S9) of the newly designed viologen compounds in 2 M KCl solution1.54 M for MDV, 0.78 M for ADV, 0.90 M for ABV, and 0.88 M for EtDVare of sufficient level for AORFB applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis of EDV was reported previously. 63 The synthesis of MDV was carried out by subsequent methylation of 4,4′-bipyridine with methyl iodide and n-decyl bromide with subsequent ion exchange to Br − by repetitive precipitations with NH 4 PF 6 and Oct 4 NBr. The synthesis of ABV was carried out by subsequent alkylation of 4,4′-bipyridine with benzyl bromide and (3-bromopropyl)trimethylammonium bromide.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this solution was applied in a full cell, using a ferrocene derivative as the active species in the positive electrolyte, they achieved 59.8% EE at 40 mA cm −2 . Korshunov et al [151] reported the employment of (2-hydroxypropyl)-β-cyclodextrin with 1-decyl-1ethyl-4,4 -bipyridinium dibromide as a host-guest complex to enhance the performance of the viologen negative electrolyte. When this new negative electrolyte was tested in a cell with (ferrocenylmethyl)trimethylammonium chloride (FcNCl) solution in the positive electrolyte, they reached an EE higher than 62% at 13.33 mA cm −2 for 500 cycles with a capacity fade rate of 3.7 × 10 −2 % per cycle.…”
Section: Organic Aqueousmentioning
confidence: 99%